Association Between a History of Nontyphoidal Salmonella and the Risk of Systemic Lupus Erythematosus: A Population-Based, Case-Control Study - Tu, Ting-Yu; Yeh, Chiu-Yu; Hung, Yao-Min; Chang, Renin; Chen, Hsin-Hua; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Objective We investigated the correlation between nontyphoidal Salmonella (NTS) infection and systemic lupus erythematosus (SLE) risk. Methods This case-control study comprised 6,517 patients with newly diagnosed SLE between 2006 and 2013. Patients without SLE were randomly selected as the control group and were matched at a case-control ratio of 1:20 by age, sex, and index year. All study individuals were traced from the index date back to their NTS exposure, other relevant covariates, or to the beginning of year 2000. Conditional logistic regression analysis was used to analyze the risk of SLE with adjusted odds ratios (aORs) and 95% confidence intervals (CIs) between the NTS and control groups. Results The mean age was 37.8 years in the case and control groups. Females accounted for 85.5%. The aOR of having NTS infection were significantly increased in SLE relative to controls (aOR, 9.20; 95% CI, 4.51-18.78) in 1:20 sex-age matching analysis and (aOR, 7.47; 95% CI=2.08-26.82) in propensity score matching analysis. Subgroup analysis indicated that the SLE risk was high among those who dwelled in rural areas; had rheumatoid arthritis, multiple sclerosis, or Sjogren’s syndrome; and developed intensive and severe NTS infection during admission. Conclusions Exposure to NTS infection is associated with the development of subsequent SLE in Taiwanese individuals. Severe NTS infection and other autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, or Sjogren’s syndrome also contributed to the risk of developing SLE.